REGULATORY AUTONOMY OF DEVELOPING COUNTRIES IN THE INTERNATIONAL TRADE LEGAL SYSTEM: NORMATIVE AND INSTITUTIONAL CHALLENGES - Abdul Razak Nasution; Muhammad Juang Rambe; Rahul Ardian Fikri (RADJA PUBLIKA, 2024)
This study examines the legal relationship between trade liberalization commitments within the framework of the World Trade Organization (WTO) and the right of developing countries to regulate. The expansion of the WTO’s scope into domestic jurisdictions has legal implications for the policy space of developing countries in the process of formulating national legislation, particularly in the sectors of public health and environmental protection. Using a doctrinal legal research methodology, this study examines general exceptions, Special and Differential Treatment (S&DT), and the jurisprudence of the Dispute Settlement Body (DSB). The research findings outline three key points. First, legal recognition of regulatory autonomy is subject to certain normative limitations. The necessity test and empirical standard of proof under the SPS and TBT Agreements create an imbalance in the burden of proof for developing countries, which has the potential to affect the sustainability of the national legislative process (regulatory chill). Second, the S&DT principle, formulated to accommodate differences in economic capacity, tends to be declaratory in its application. This results in limitations on the binding force of the instrument as a legal basis for defense in dispute resolution. Third, legal interpretations by dispute settlement bodies have direct legal consequences for domestic autonomy. Furthermore, administrative constraints at the Appellate Body level and the implementation of the Multi-Party Interim Appeal Arbitration Arrangement (MPIA) also affect the fulfillment of the principle of legal certainty at the appellate stage. This study concludes that the formulation of national legislation requires the fulfillment of a pre-formulation feasibility review (ex-ante assessment). Additionally, multilateral harmonization efforts are needed to fundamental legal justification.